The microbial consortia directed evolution towards plastic degradation – the key to waste management? - SIDHU, GURPREET KAUR; Chandel, Pooja (JOURNAL OF ADVANCES IN BIOLOGY, 2019)
The rampant use of plastics and their disposal into waste are adding to the problems of pollution. The resistance of plastics to bio-degradation is an added advantage for its significant use but the same property creates havoc when the plastic products are disposed off as waste in massive amounts. The property of micro-organisms to evolve quickly brings answers to even the most impossible situations. The current and several other reports show that the plastic is bio-degradable. The current report shows the action of consortia of microbes isolated from a plastic dumping site can lead to degradation of the polymer. The microbial consortia isolated from plastic dumping site when made to grow in controlled conditions in presence of basal media with plastic as sole source of carbon for an extended period of time, aberrations were observed on surface of the plastic. The proteins reported till date in plastic degradation when analysed in-silico for their homologs in all domains of life, they were found to be significantly similar to proteins of cutinase, hydrolase, lipase and some hypothetical proteins. This shows that the plastic degrading proteins have possibly evolved from these protein families.